2022
DOI: 10.1101/2022.07.24.501124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion of the Catalytic Repertoire of Alcohol Dehydrogenases in Plant Metabolism

Abstract: Medium-chain alcohol dehydrogenases (ADHs) comprise a highly conserved enzyme family that catalyse the reversible reduction of aldehydes. However, recent discoveries in plant natural product biosynthesis suggest that the catalytic repertoire of ADHs has been expanded. Here we report the crystal structure of dihydroprecondylocarpine acetate synthase (DPAS), an ADH that catalyses the non-canonical 1,4 reduction of an α,β-unsaturated iminium moiety. Comparison with structures of plant-derived ADHs that catalyse 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…We isolated isotopically labeled (–)-tabersonine ( 2 ), Ψ-tabersonine ( 5 ), and Ψ-vincadifformine ( 9 ) and showed that the deuterium labels were incorporated at carbon 19 for (–)-tabersonine ( 2 ) as expected, 13 carbons 19 and 21 for Ψ-tabersonine ( 5 ), carbons and 19, 21, 15 for Ψ-vincadifformine ( 9 ) ( Figure 4) . We performed CD spectroscopy of these isolated products and assigned the stereochemistry as (+)-Ψ-tabersonine ( 5 ) and (+)-Ψ-vincadifformine ( 9 ), which is the expected stereochemistry based on the downstream ibophyllidine products (Figure S16).…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…We isolated isotopically labeled (–)-tabersonine ( 2 ), Ψ-tabersonine ( 5 ), and Ψ-vincadifformine ( 9 ) and showed that the deuterium labels were incorporated at carbon 19 for (–)-tabersonine ( 2 ) as expected, 13 carbons 19 and 21 for Ψ-tabersonine ( 5 ), carbons and 19, 21, 15 for Ψ-vincadifformine ( 9 ) ( Figure 4) . We performed CD spectroscopy of these isolated products and assigned the stereochemistry as (+)-Ψ-tabersonine ( 5 ) and (+)-Ψ-vincadifformine ( 9 ), which is the expected stereochemistry based on the downstream ibophyllidine products (Figure S16).…”
mentioning
confidence: 57%
“…The (-)-tabersonine (2) product produced by TiTabS had no deuterium incorporation, as expected; for-mation of Ψ-tabersonine (5) and Ψ-vincadifformine (9) from angryline (1a) showed incorporation of one and deuterium atoms respectively and was strictly dependent upon the presence of both reductase, TiDPAS1, and dase, PAS (Figure S15). We isolated isotopically labeled (-)-tabersonine (2), Ψ-tabersonine (5), and Ψ-vincadifformine (9) and show that the deuterium labels were incorporated at carbon 19 for (-)-tabersonine (2) as expected, 13 carbons 19 and for Ψ-tabersonine (5), carbons and 19, 21, 15 for Ψ-vincadifformine (9) (Figure 4). We performed CD spect copy of these isolated products and assigned the stereochemistry as (+)-Ψ-tabersonine ( 5) and (+) vincadifformine (9), which is the expected stereochemistry based on the downstream ibophyllidine products (F ure S16).…”
mentioning
confidence: 58%
See 3 more Smart Citations